Purification and characterization of the soluble form of the receptor for advanced glycation end-products (sRAGE): a novel fast, economical and convenient method - Kumar, Varun; Sulaj, Alba; Fleming, Thomas; Nawroth, Peter Paul (Experimental and clinical endocrinology & diabetes, 2017)
The receptor for advanced glycation end-products (RAGE) is a multi-ligand receptor which belongs to the pattern recognition receptor family and can bind to various ligands such as advanced glycation end-products (AGEs), members of the S100 protein family, glycosaminoglycans, amyloid β peptides, high-mobility group box-1 (HMGB1) and nucleic acids through its extracellular domain. The RAGE-ligand interaction leads to the activation of MAP kinase and NF-kB signaling pathways. Further ligand-induced up-regulation of RAGE is involved in various patho-physiological situations including late diabetic complications, Alzheimer disease and several other neurodegenerative diseases. A secreted soluble isoform of RAGE (sRAGE), corresponding to the extracellular domain only, has the ability to block RAGE-associated cellular activation and signaling. Further application of recombinant sRAGE has been shown to block RAGE-mediated pathophysiological conditions in various models of cancer or multiple sclerosis. These finding demonstrates sRAGE as a therapeutic tool to block RAGE-associated inflammatory signaling. In this manuscript, we describe a two-step simple, novel and convenient method for expressing and purifying scalable quantities of biologically active murine form of sRAGE by using E.coli as an expression host. The method we propose has several advantages over the current available methods particularly in terms of yield and quality of preparation. The sRAGE produced by this expression system retains all the secondary structural properties as analyzed by the ligand binding affinities. The produced protein also retains all the DNA-RAGE binding functional properties and thus can be a valuable tool for studying dynamics of this novel RAGE ligand. Moreover this method can be utilized by researchers to generate biologically active endotoxin-free sRAGE for in vivo applications to study and treat RAGE-associated pathologies.